Domniemanie czy definicja zgodności towaru z umową: [Presumption versus definition of the conformity of the product with the contract] (Studia Prawnicze / The Legal Studies, 2012)
Artykuł 4 ust. 2 i 3 ustawy z dnia 27 lipca 2002 r. o szczególnych warunkach sprzedaży konsumenckiej oraz zmianie Kodeksu cywilnego (Dz.U. Nr 141, poz. 1176, z 2002 r.), podobnie jak art. 2 ust. 2 implementowanej tą ustawą dyrektywy,2 odwołuje się do pojęcia domniemania zgodności towaru z umową. W polskiej doktrynie pojawiły się jednak wątpliwości odnośnie do przyjętych w tych aktach rozwiązań prawnych: tylko nieliczni autorzy pozostają przy konstrukcji domniemania, większość stoi na stanowisku, że mamy tutaj do czynienia z jakimś rodzajem ustawowej definicji niezgodności. Ponieważ zaś definicja legalna a domniemanie prawne to dwie zupełnie różne instytucje, prawidłowe zrozumienie postanowień ustawy (i dyrektywy) posiada istotne znaczenie zarówno z punktu widzenia teorii, jak i praktyki. The article addresses the issue of the concept of the nonconformity of the product with the contract in the context of consumer sale. Specifically, it brings up the question whether the directive no. 1999/44/WE and the Polish statutes regarding consumer sale introduce the strict definition or the rebuttable presumption of the conformity of the product with the contract. That question is of paramount importance since the definition means here that in the circumstances outlined in the directive/statute acquired goods are in conformity with the contract and the consumer cannot prove the contrary. The presumption, in turn, is tantamount to the assertion that the occurrence of these circumstances indicates the state of the conformity with the contract, but not in the definite way. That is, the interested party may nonetheless make an effort to establish that the product does not conform to the contract. Despite the clear meaning of the pertinent provisions of the statute and directive, most of Polish scholars maintain that, in consumer sale, we deal withthe definition of the nonconformity of the product with the contract. The Author strongly disagrees with them, arguing for the concept of the rebuttable presumption. However, according to him, due to the need of legal certainty and efficacy, the rebuttal should be possible here only in exceptional cases. Incidentally, the same concerns the proving of the conformity of contract when not all of the circumstances mentioned in the presumption are present.